Dentofacial Orthopaedic Correction of Maxillary Retrusion with the Protraction Facemask - a literature review - Goh GekKiow; Kaan Sheung K (Sciendo, 1992)
The retruded maxilla in the Class III skeletal pattern could be effectively corrected with the protraction facemask in selected cases. A review of the different types of orthopaedic appliances used in Class III treatment, the rationale for facemask therapy, the effect of this treatment and the factors affecting stability is presented.